Effects of Paracentrotus lividus (Lamark, 1816) harvesting on benthic assemblages. An experimental approach. (22nd October 2019) - Torres, Ana Catarina; Rubal, Marcos; Sousa‐Pinto, Isabel; Veiga, Puri
Abstract: The effect of harvesting on the diversity and structure of benthic assemblages is nowadays a relevant component of fishery management. Invertebrate harvesting is increasing worldwide and sea urchins are one of the main invertebrate target species. However, current knowledge about the effects of sea urchin harvesting on benthic assemblages is still poor. The aim of this study is to evaluate the influence of Paracentrotus lividus (Lamark, 1816) harvesting on tide pool assemblages from intertidal rocky shores. To achieve this objective, a field removal experiment was done for 10 months. Results of univariate and multivariate analyses showed that P. lividus harvesting had a significant effect on the number of taxa and structure of the benthic assemblage. Assemblages from pools where P. lividus were removed showed significant differences against controls; namely, where P. lividus were eliminated, pools showed higher number of taxa than control pools. This result contrasts with previous studies assessing effects of invertebrate harvesting that generally have found a biodiversity reduction in the exploited habitat. Despite this apparently positive effect of P. lividus harvesting, we should be cautious because effects of P. lividus harvesting on higher trophic levels or during long periods of time remain unexplored.